PERSEPSI SISWA TERHADAP TUTURAN IMPERATIF GURU DALAM INTERAKSI BELAJAR MENGAJAR BAHASA INDONESIA DI SMP NEGERI 3 SUNGGUMINASA - Harnum, Ade; Anshari; Usman (Journal of Applied Linguistics and Literature, 2024)
This research is a quantitative descriptive study that aims to describe students' perceptions of teacher imperative speech in teaching and learning interactions in Indonesian at SMP Negeri 3 Sungguminasa. The method used in this study is a survey method with data collection techniques using questionnaires. The population in this study was all class VIII students of SMP Negeri 3 Sungguminasa as many as 331 students, while the sample was 60 students. The research data was obtained by distributing questionnaires in hardcopy form to students. The results of the accumulation state that the indicator of attention is on the "positive" criterion with a percentage of 85%. On the indicators of student learning motivation, it meets the criteria of "very positive" with a percentage of 88%. On the indicator of teaching methods of teachers meet the criteria of "very positive" with a percentage of 86%. Meanwhile, the overall accumulated results stated that students' perceptions of teacher imperative speech were on the "very positive" criterion with a percentage of 86%. Based on these results, it was concluded that students of SMP Negeri 3 Sungguminasa have a very positive perception of teacher imperative speech in teaching and learning interactions Indonesian.